Chapter Prefixation in the Rise of Slavic Aspect - Dickey, Stephen (Biblioteca di Studi Slavistici, 2017)
This paper investigates the role that prefixes played in the development of the Slavic aspect category utilizing concepts from dynamic systems theory. It is argued that the bleaching of the prefix u- was crucial in the development of the perfectivizing function of Common Slavic prefixes, and that the semantic concept of change of state functioned as an attractor in the development of the network of prefixes and the aspect category as a whole.